Effect of Light Provision on Growth Characteristics of Japanese Native Herbs for Indoor Greening - Ayako Nagase (HortScience, 2024)
Indoor greening is becoming popular because it provides many benefits for people. However, plant selection for indoor greening is limited to shade-tolerant tropical plants internationally, and little research has been performed to expand the use of native herb plant species. The aim of this research was to study growth characteristics of Japanese native herbs under common light intensity regimes in office buildings. Eight species of Japanese native herbs (Acorus gramineus, Cameilla sinensis, Farfugium japonicum, Gynostemma pentaphyllum, Perilla frutescens var. crispa f. viridis, Petasites japonicus, Sasa veitchii, and Saxifraga stolonifera) were examined in an open growth chamber with light-emitting diode light tape under three light intensities [photosynthetic photon flux densities of 3 µmol·m−2·s−1 (250 lx), 6 µmol·m−2·s−1 (500 lx), and 12 µmol·m−2·s−1 (750 lx)] from 8 AM to 10 PM every day from Jun 2021 to Oct 2021 in an office. Farfugium japonicum and Saxifraga stolonifera were as shade-tolerant as typical tropical plants and grew well under all light intensities. Sasa veitchii performed well under high and medium light intensity. The other plant species require supplemental lightning to achieve sufficient growth indoors.